(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Hypospadias may be associated with other congenital upper urinary tract anomalies. Literature showed various opinions to evaluate or not to evaluate upper urinary tract in hypospadias patient. Frequency of upper urinary tract anomalies also varies. This study was carried out on this background to avoid confusion. Objectives: Morphological evaluation of upper urinary tract to find out the frequency of upper urinary tract anomalies associated with uncomplicated hypospadias patients and give a guideline for investigation of such patients. Methods: This prospective study was designed and accomplished in the Departments of Paediatric Surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka; Dhaka Medical College Hospital (DMCH), Dhaka and Chittagong Medical College Hospital (CMCH), Chittagong; Bangladesh from October 2004 to June 2006. Eighty five (85) patient with hypospadias having neither any congenital anomalies, nor other genital ambiguity, nor any secondary vesicoureteric reflux (VUR) or meatal stenosis were selected for the study. Detailed history and examination were carried out. Upper urinary tract of all patients were evaluated by Ultrasonography (USG), Intravenous Urography (IVU), and Micturating Cystourethrography (MCU).To exclude genital ambiguity in perineal hypospadias, karyotype were done to ascertain male sex. Results were analyzed by SPSS with the help of Chi-square and Z approximation test . Result : Eighty five (85) patients were taken. All patients were evaluated by USG, IVU and MCU to detect congenital upper urinary tract anomalies. Results: Four (4) patients had had upper urinary tract anomalies. One (1) patient found to have left sided pelviureteric junction obstruction (PUJO) while one (1) patient had right sided pelviureteric junction obstruction (PUJO). One (1) patient was found to have left sided pelviureteric duplication and the last patient with left renal agenesis. USG detected three (3) anomalies in 85 patients (3.53%) and IVU detected all four (4) anomalies in 85 patients (4.7%), but no primary reflux was detected by MCU. Overall frequency of upper urinary tract anomalies was 4.7%. Eighty one (81) patients (95.3%) had no anomalies. USG detected 3 (three) anomalies out of 4 (four) patients (75%) & IVU detected all four anomalies (100%). Absence of upper urinary tract anomaly was statistically significant. Conclusion: Frequency of upper urinary tract anomalies are significantly low (4.7%) in uncomplicated hypospadias. USG can detect 75% congenital upper urinary tract anomalies in hypospadias patients. So USG is good enough and recommended to evaluate upper urinary tract anomalies in uncomplicated hypospadias patients. There is no need to evaluate upper urinary tract by IVU or MCU in such patients, if asymptomatic otherwise. DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19547